1979
DOI: 10.1002/chin.197916156
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: BUTADIENE VIA OXIDATIVE DEHYDROGENATION

Abstract: Die Petro‐Tex beschreibt die seit 1965 kommerziell bewährte oxidative Dehydrierung (Oxo‐D) von n‐Buten im Gemisch mit Wasserdampf, Luft oder Sauerstoff an einem Fixbettreaktor zu Butadien.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 0 publications
0
9
0
1
Order By: Relevance
“…Only 5% reduction of the n-butene conversion was observed after 2600 hours (not shown here). The possibility of catalyst deactivation by carbon deposition seems to be low because the carbonaceous residue can be removed from the catalyst surface by reaction with steam [12], which shows the autoregenative nature of the catalyst [1].…”
Section: Catalyst Deactivationmentioning
confidence: 99%
See 3 more Smart Citations
“…Only 5% reduction of the n-butene conversion was observed after 2600 hours (not shown here). The possibility of catalyst deactivation by carbon deposition seems to be low because the carbonaceous residue can be removed from the catalyst surface by reaction with steam [12], which shows the autoregenative nature of the catalyst [1].…”
Section: Catalyst Deactivationmentioning
confidence: 99%
“…Among them, the oxygen to n-butene ratio is the most important variable because the 1,3-butadiene yield is greatly affected by the oxygen level used [1]. As the oxygen to n-butene ratio increases, higher n-butene conversion is expected at the expense of 1,3-butadiene selectivity.…”
Section: Catalyst Deactivationmentioning
confidence: 99%
See 2 more Smart Citations
“…With the promising aspect of the oxidative dehydrogenation reaction, there have been a lot of studies since the early 1970s [2][3][4][5][6][7][8]. Recently, Song et al [9][10][11] have focused on the preparation of two types of catalysts such as ferrite catalysts and multicomponent bismuth molybdate catalysts [12][13][14][15][16][17][18][19][20][21][22][23][24] and found that catalytic performance could be improved by pH control [9,15,20], divalent metal substitution [11], or calcination condition [24].…”
Section: Introductionmentioning
confidence: 99%